Literature review on breast cancer-related lymphedema and related factors - Shamoun, Shaimaa; Ahmad, Muayyad (Archive of Oncology, 2023)
A potential complication that affects a patient’s quality of life is breast cancer-related lymphedema (BCRL). Due to lymphatic system failure brought on by breast cancer treatment, it is secondary lymphedema. This literature review examines 50 articles that are connected to BCRL. Research conducted in the English language between 2017 and 2022 is included. The definition, occurrence, severity, symptoms, risk factors, aspects of quality of life, and total decongestive therapy are all incorporated in this review of BCRL. The severity of the BCRL is assessed using International Staging Lymphology, 2020 from mild to severe. The documented incidence rates of BCRL in the literature range greatly, between less than 5% and more than 50%. The most significant risk factors of BCRL are related to lymph node surgery, in particular, axillary lymph node excision, and radiation therapy. If BCRL is not properly diagnosed and managed, it could have debilitating, long-lasting and late crippling side-effects of breast cancer treatment. It frequently has a devastating impact on the quality of life in many domains. To better understand the behaviors and management of lymphedema risk reduction, patients with breast cancer need extra information. To evaluate the effectiveness of complete decongestive therapy as a risk reduction behavior rather than for management and treatment, more study needs be done with a larger sample and longer supervision. Keywords: breast cancer, lymphedema, skin care, treatment, compression